Tropical cyclones expand faster at warmer relative sea surface temperature - Danyang Wang; Daniel R. Chavas; Benjamin A. Schenkel (Proceedings of the National Academy of Sciences, 2025)
Tropical cyclones are expected to intensify more rapidly with warming, but relatively little work has examined whether they could expand more rapidly with warming, too. Recent theory predicts that peak expansion rate should increase with sea surface temperature (SST), and physical arguments suggest this dependence should be specifically on the relative SST, i.e. the SST difference from the tropical mean. We test this hypothesis with historical observational data, in which SST variations are primarily variations in relative SST. Both average and peak expansion rates are found to systematically increase with relative SST globally across the Northern Hemisphere (27.2 and 37.5 km/d/K) and within each individual basin. Results are robust across both reanalysis and Best Track observational datasets. Uniform-SST aquaplanet simulations show a much weaker dependence of maximum expansion rate on absolute SST, suggesting that the dominant dependence is on relative SST. Hence, mean global warming is not expected to strongly change storm size dynamics, but patterns of sea surface warming may play an important role in determining how storm size, and hence coastal risk, may change in the future. This work can also help improve forecasting of the wind field and its hazards and impacts at landfall.